Deciphering the Binding of Natural Terpenoids to Mycobacterium tuberculosis Type III Polyketide Synthase18 (PKS18): An In-Silico Approach - Akanksha Sharma, Mohammad Hayatul Islam, Nida Fatima, Tarun K. Upadhyay, M. Kalim A. Khan, Upendra N. Dwivedi, Rolee Sharma (Journal of Applied Pharmaceutical Science, 2018)
Tuberculosis (TB) is a major cause of death across the globe and kills 1.5 million people per annum, thereby persisting as a challenge for the scientific community. Although the ‘Directly Observed Treatment, Short Course’ chemotherapy (DOTS) is an internationally recommended approach for TB, the treatment regimen is long and arduous, making patient compliance difficult. This has led to the occurrence of antibiotic confrontation, creating a need for the identity of novel drug lead(s) towards new targets identified in Mycobacterium tuberculosis (M.tb.). The current study was undertaken with this objective directed towards the identification of potential drug candidate(s) for TB therapy using an in silico approach against PKS18, a mycobacterial enzyme essential for its intracellular survival, pathogenicity and drug resistance. In the present study, 672 natural terpenoids from plants, algae, bacteria, fungi and marine sponges were compiled and put through in silico pharmacokinetic analysis in term of absorption, distribution, excretion, and toxicity (ADMET) to explore their drugability properties. Pharmacokinetic analyses revealed that 18 plant-derived and 1 marine sponge-derived natural compounds satisfy all the ADMET criterion and also those of Lipinski’s Rule of Five. These natural compounds docked successfully within the active site of type III polyketide synthase18 (PKS18) and exhibited low binding energy indicating high affinity. In addition, docking was also performed with commercially available first-line TB drugs including rifampicin, isoniazid, ethambutol, and pyrazinamide to compare the binding efficacy with that of the selected natural compounds. Of the compounds tested, vulgarin showed the best docking profile, followed by alisiaquinone A, 12-Deoxyphorbol-13-angelate-20-acetate and cynaropicrin.
Keywords: Tuberculosis, terpenoids, molecular docking, ADMET and type III polyketide synthase 18.